Density-induced reentrant melting of colloidal Wigner crystals. Issue 7 (27th January 2016) - Everts, J. C.; Boon, N.; van Roij, R.
Abstract : By using projections of the colloid–ion mixture to a system of (soft) repulsive spheres and the one-component plasma, we explain the experimentally observed reentrant melting of electrostatically repelling colloids upon increasing the colloid density. Abstract : Electrostatic repulsions can drive crystallization in many-particle systems. For charged colloidal systems, the phase boundaries as well as crystal structure are highly tunable by experimental parameters such as salt concentration and pH. By using projections of the colloid–ion mixture to a system of (soft) repulsive spheres and the one-component plasma (OCP), we study the hitherto unexplained experimentally observed reentrant melting of electrostatically repelling colloids upon increasing the colloid density. Our study shows that the surface chemistry should involve a competition between adsorption of cations and anions to explain the observed density-induced reentrant melting.